2017
DOI: 10.1002/jcp.25818
|View full text |Cite
|
Sign up to set email alerts
|

SUMO‐modified insulin‐like growth factor 1 receptor (IGF‐1R) increases cell cycle progression and cell proliferation

Abstract: Increasing number of studies have shown nuclear localization of the insulin‐like growth factor 1 receptor (nIGF‐1R) in tumor cells and its links to adverse clinical outcome in various cancers. Any obvious cell physiological roles of nIGF‐1R have, however, still not been disclosed. Previously, we reported that IGF‐1R translocates to cell nucleus and modulates gene expression by binding to enhancers, provided that the receptor is SUMOylated. In this study, we constructed stable transfectants of wild type IGF1R (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Melatonin reduced the expression of SUMO‐1 more than SUMO‐2 and SUMO‐3 in X02 cells by qRT‐PCR (Figure A). As it was well‐known that many proteins including p53, c‐Myc, and others can be sumoylated, SUMOylation of nestin was investigated in X02 cells. Interestingly, SUMO‐1 overexpression upregulated the expression of nestin, without affecting c‐Myc, and also reduced the inhibitory effect of melatonin on nestin and c‐Myc in X02 cells transfected with HA‐SUMO‐1 plasmid (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin reduced the expression of SUMO‐1 more than SUMO‐2 and SUMO‐3 in X02 cells by qRT‐PCR (Figure A). As it was well‐known that many proteins including p53, c‐Myc, and others can be sumoylated, SUMOylation of nestin was investigated in X02 cells. Interestingly, SUMO‐1 overexpression upregulated the expression of nestin, without affecting c‐Myc, and also reduced the inhibitory effect of melatonin on nestin and c‐Myc in X02 cells transfected with HA‐SUMO‐1 plasmid (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Further confirmation was achieved by using R-TSM cells (RϪ transfected with triple SUMO-site-mutated IGF-1R cell line). Just recently we showed that R-TSM cells exhibited diminished nuclear gene regulatory effects of IGF-1R while retaining IGF-1R kinase-dependent signaling (2,24).…”
Section: Nuclear Igf-1r-mediated Phosphorylation Marks Pcna For Ubiqumentioning
confidence: 96%
“…MEF igf1r Ϫ/Ϫ (RϪ-) and RϪ cells overexpressing IGF-1R (Rϩ) were from Dr. R. Baserga (Thomas Jefferson University, PA). The R-WT (RϪ with newly transfected WT IGF-1R), R-TSM (RϪ transfected with SUMOmutated IGF-1R), and RϪPuro (empty vector control) were obtained as described elsewhere (24). All cell lines were cultured in DMEM with 10% FBS, with the exception of Gm02808 being cultured in DMEM/F-12 with 20% FBS.…”
Section: Cell Culturesmentioning
confidence: 99%
“…It has been reported that nuclear IGF-IR is a feature of pre-invasive lesions and invasive cancers including prostate, renal and breast cancers, and an association between nuclear IGF-IR and adverse prognosis was identified in renal cancer [79]. Subsequent data did associate nuclear IGF-IR with proliferation, tumorigenicity, resistance to EGFR inhibition and clinical response to therapeutic anti-IGF-IR antibodies, which suggests that IGF-IR nuclear import has biological significance and may contribute directly to IGF-IR function [79,[85][86][87][88][89][90].…”
Section: The Nuclear Translocation Of the Igf-ir And Irs And Its Signmentioning
confidence: 99%